The genus Ozineus Bates, 1863 in South America (Coleoptera, Cerambycidae, Lamiinae) - Monné, Marcela L.; Monné, Miguel A.; de Santana Souza, Diego (Zootaxa, 2019)
The diagnosis of Ozineus Bates, 1863 is emended and a key is provided for the species of the genus in South America. A new synonymy is proposed for Sternacutus Gilmour, 1961 (junior synonym of Ozineus Bates, 1863), which includes a new combination for Sternacutus zikani (Melzer, 1935). Tropidozineus albidus Monné, 2009 is transferred to Ozineus.